Prospective randomized investigation of topical anesthesia during unilateral laparoscopic ovariectomy in horses. (21st June 2019) - Koch, Drew W.; Easley, Jeremiah T.; Hatzel, Jennifer N.; Nelson, Brad B.; Hendrickson, Dean A.; Bruemmer, Jason; Hackett, Eileen S.
Abstract: Objective: To compare pain‐related responses in mares receiving topical or injected anesthesia of the ovarian pedicle prior to standing unilateral laparoscopic ovariectomy. Study design: Prospective randomized, blinded, placebo‐controlled study. Animals: Fifteen healthy research mares. Methods: Mares were restrained in stocks and administered sedation. A right or left paralumbar ovariectomy was performed by using a laparoscopic portal and two instrument portals. Mares were divided into two treatment groups, and equal volumes of mepivacaine anesthesia were administered either topically (n = 8) or by injection into the ovarian pedicle (n = 7). Saline controls were simultaneously administered topically (n = 7) or by injection (n = 8), and surgeons were blinded to the treatment group. Ovarian removal was performed with traumatic forceps and a blunt tip vessel sealer and divider. Pain responses were measured by operative visual analog scale (VAS) scoring and perioperative serum cortisol response. Visual analog scale and serum cortisol were compared between groups by using Mann–Whitney testing. Serum cortisol concentrations were evaluated using repeated‐measures one‐way analysis of variance. Results: Ovaries were removed in all mares by using the described technique without operative complications. Quantity of sedation required to complete the procedure, operative VAS scores, and perioperative cortisol concentrations did not differ between treatment groups. Conclusion: Application of topical mepivacaine to the ovary provided intraoperative analgesia similar to injection of the ovarian pedicle when performing unilateral standing laparoscopic ovariectomy in mares. Clinical significance: Topical anesthesia application to the ovary could provide an alternative to laparoscopic needle use, reducing the risk of inadvertent trauma to the pedicle or other visceral organs during laparoscopic ovariectomy.